2022
DOI: 10.3389/fpsyt.2022.1016735
|View full text |Cite
|
Sign up to set email alerts
|

Increased plasma levels of IL-6 are associated with striatal structural atrophy in major depressive disorder patients with anhedonia

Abstract: BackgroundAnhedonia, as the core endophenotype of major depressive disorder (MDD), is closely related to poor prognosis, but the mechanism of this feature remains to be understood. The aim of this study was to investigate the inflammatory factors and brain structural alterations in MDD patients with anhedonia and evaluate the relationship between these factors.MethodsWe assessed the plasma levels of interleukin-1 beta (IL-1β), interleukin-6 (IL-6) and tumor necrosis factor alpha (TNF-α) in MDD patients with an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 66 publications
0
4
0
Order By: Relevance
“…The general exclusion criteria were as follows: (1) existence of any major medical disease, including cardiovascular, respiratory, endocrine and neurological diseases (e.g., epilepsy, brain trauma and stroke); (2) current use of any medication that might affect the central nervous system; (3) drug or alcohol dependence or abuse; (4) female with pregnancy; (5) with histories of psychotherapy and physical therapy, such as transcranial direct current stimulation (tDCS), transcranial magnetic stimulation (TMS), and electroconvulsive therapy (ECT); and (6) contraindications to MRI scan, including retractors or braces, metallic implants, and claustrophobia. The present study is one of our serial investigations focusing on MDD, and the recruitment of participants has been described in our previous studies [ 33 35 ]. This study was approved by the local Medical Ethics Committee of The First Affiliated Hospital, Zhejiang University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The general exclusion criteria were as follows: (1) existence of any major medical disease, including cardiovascular, respiratory, endocrine and neurological diseases (e.g., epilepsy, brain trauma and stroke); (2) current use of any medication that might affect the central nervous system; (3) drug or alcohol dependence or abuse; (4) female with pregnancy; (5) with histories of psychotherapy and physical therapy, such as transcranial direct current stimulation (tDCS), transcranial magnetic stimulation (TMS), and electroconvulsive therapy (ECT); and (6) contraindications to MRI scan, including retractors or braces, metallic implants, and claustrophobia. The present study is one of our serial investigations focusing on MDD, and the recruitment of participants has been described in our previous studies [ 33 35 ]. This study was approved by the local Medical Ethics Committee of The First Affiliated Hospital, Zhejiang University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…Namely, “agree” or “strongly agree” was recorded as a score of 0, while “disagree” or “strongly disagree” was recorded as 1. The total score after conversion to > 5 could distinguish the presence or absence of severe anhedonia, which was used in some previous studies [ 35 , 39 ]. In this study, we defined severe anhedonia as a dichotomous variable with a SHAPS score > 5 and calculated the raw total scores of the SHAPS scale for MDD patients to assess the severity of anhedonia.…”
Section: Methodsmentioning
confidence: 99%
“…The general exclusion criteria for all subjects were as follows: (1) existence of any major medical disease including cardiovascular, respiratory, endocrine and neurological diseases (e.g., epilepsy, brain trauma, and stroke); (2) current use of any medication that might affect the central nervous system, (3) drug or alcohol dependence or abuse; (4) female with pregnancy; (5) with histories of psychotherapy and physical therapy, such as transcranial direct current stimulation (tDCS), transcranial magnetic stimulation (TMS), and electroconvulsive therapy (ECT); 6) contraindications to MRI scan, including retractors or braces, metallic implants, and claustrophobia. The present study is one of our serial investigations focusing on MDD and the recruitment of participants has been described in our previous studies [ 33 35 ]. This study was approved by the local Medical Ethics Committee of The First Affiliated Hospital, Zhejiang University School of Medicine.…”
Section: Methodsmentioning
confidence: 99%
“…Boufidou et al demonstrated a relationship between the levels of IL-6 in the cerebrospinal fluid and symptoms of depression within the first 4 days after childbirth (p = 0.035) (39). Other authors reported elevated serum IL-6 levels in patients with anhedonia and a major depressive episode (40).…”
Section: Interleukins and Depressionmentioning
confidence: 98%